Jack of Fables. [6], The big book of war - Willingham, Bill (DC Comics, 2009)
"When Bookburner's army attacks Revise's compound, Jack returns not as a prisoner but as Commander-in-Chief. [... S]ecrets are revealed, including the strange relationships between Jack and the Page sisters"--From publisher's web site.